ATLAS search for a heavy gauge boson decaying to a charged lepton and a neutrino in pp collisions at √s =7 TeV - Alonso, Francisco (2012)
The ATLAS detector at the LHC is used to search for high-mass states, such as heavy charged gauge bosons (W'), decaying to a charged lepton (electron or muon) and a neutrino. Results are presented based on the analysis of pp collisions at a center-of-mass energy of 7 TeV corresponding to an integrated luminosity of 4.7 fb−1. No excess beyond Standard Model expectations is observed. A W' with Sequential Standard Model couplings is excluded at the 95 % credibility level for masses up to 2.55 TeV. Excited chiral bosons (W*) with equivalent coupling strength are excluded for masses up to 2.42 TeV.